Elderly caregivers of the elderly: frailty, loneliness and depressive symptoms - Ariene Angelini dos Santos-Orlandi; Allan Gustavo Brigola; Ana Carolina Ottaviani; Bruna Moretti Luchesi; Érica Nestor Souza; Fernanda Gomez de Moura; Juliana de Fátima Zacarin; Mariélli Terassi; Nathalia Alves de Oliveira; Sofia Cristina Iost Pavarini
ABSTRACT Objective: to investigate the association between frailty, loneliness and depressive symptoms of elderly caregivers. Method: a cross - sectional study carried out with 341 elderly caregivers enrolled in Family Health Units of a city in the countryside of São Paulo State. The interviews were domiciliary and included questionnaire for characterization of the caregiver, Fried's frailty phenotype, family APGAR (family functionality), Geriatric Depression Scale (depressive symptoms) and item 3 of the Herth Hope Scale (loneliness). Logistic regression was used to analyze the association between depressive symptoms and solitude (independent variables), and frailty and pre-frailty (dependent variables). Results: there was an association between frailty, loneliness and depressive symptoms. Elderly caregivers had increased odds of 158% presenting pre-frailty, and 360% of frailty. Elderly caregivers with depressive symptoms had an increased chance of 242% of presenting fragility. Conclusion: elderly and lonely caregivers with depressive symptoms are more likely to be frail and pre-frail.